Extending Imaging Volume in Soft X‐Ray Tomography. Issue 4 (2nd March 2023) - Ekman, Axel; Chen, Jian-Hua; Vanslembrouck, Bieke; Loconte, Valentina; Larabell, Carolyn A.; Le Gros, Mark A.; Weinhardt, Venera
Abstract : Soft X‐ray tomography offers rapid imaging of whole, single cells with a few tens of nanometers spatial resolution without fixation or labeling. Herein, this technique is limited to specimens about 10 μm thick, such that applications of soft X‐ray tomography of large human cells or multicellular specimens are not possible. A theoretical and experimental framework for soft X‐ray tomography that enables extension of imaging volumes to 18 μm‐thick specimens is developed. This approach, based on long depth of field and half‐acquisition tomography, is easily applicable to microscopes equipped with a full‐rotation specimen stage. This opens opportunities for imaging large human cells, such as those commonly seen in cancer research, as well as cell‐to‐cell interactions, where two or more cells occupy the same imaging volume. Abstract : Soft X‐ray tomography offers rapid imaging of whole, single cells with a few tens of nanometers spatial resolution without fixation or labeling. Currently, this technique is limited to specimens about 10 μm thick. A theoretical and experimental framework for soft X‐ray tomography that enables extension of imaging volumes to 18 μm‐thick specimens is presented.